Analisis Tipologi Dan Sektor Potensial Terhadap Pertumbuhan Ekonomi Di Propinsi Jawa Tengah Tahun 2013-2015 - Handayani, Ike, Dr. Didit Purnomo, SE. M.Si (2017)
This study analyzes the typology and potential sector in the economic development in the region of Central Java Province. Data is the value of GDP, the GDP per capita, the national GDP, and the total population. The results of the analysis of LQ fluctuated, occurred in the construction sector 2013-2014 sedangkat sector basis in 2015 to non-base. While the change in the non base into the basic sector is the sector provision of accommodation and eating and drinking. The results of the analysis method esteban marquillas Shift-share sector shows that have a competitive advantage and specialization are agriculture sector, kebutanan, and fishing, manufacturing, wholesale and retail trade sector; Repair of cars and motorcycles, and education services. Klassen typology which is supported by the analysis of geographic information systems in Central Java province which is included in the category of areas of fast forward and fastgrowing districts, among others Sukoharjo, Karanganyar, Semarang district, Kendal district, Surakarta, and Kendal.